USCBS Releases Statement on the Iran Conflict and Cultural Heritage - Dewan, Rachel (US Committee of the Blue Shield, 2026)
The USCBS further underscores the critical importance of advance coordination with cultural heritage professionals, deployment of cultural property protection lists, and engagement with relevant international bodies — including UNESCO and The Blue Shield International (BSI) — to safeguard at-risk sites. The destruction of cultural heritage is irreversible. It erases identity, history, and the shared memory of civilizations. No military or political objective justifies the willful or negligent destruction of humanity’s common inheritance. Such destruction is also one of the actions that can make returning to a state of peace more difficult.
Iran